2009
DOI: 10.3390/molecules14093339
|View full text |Cite
|
Sign up to set email alerts
|

A General Synthesis of C8-Arylpurine Phosphoramidites

Abstract: A general scheme for the synthesis of C8-arylpurine phosphoramidites has been developed. C8-Arylation of C8-bromo-2′-deoxyguanosine is the key step and has been achieved through the use of a Suzuki coupling. Since the coupling reaction is conducted under aqueous conditions, it is unnecessary to protect and then deprotect the hydroxyl groups, thus saving several steps and improving overall yields. Once the C8-arylgroup is introduced, the glycosidic bond becomes very sensitive to acid catalyzed cleavage. Protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
(11 reference statements)
0
20
0
Order By: Relevance
“…CD spectra were measured using a Jasco J-810 spectropolarimeter (Easton, MD). The oligonucleotides CG and CG 8Ph were prepared as previously described [24] as were the protected 8-(4-aryl)-2'-deoxyguanosine phosphoramidites needed for oligonucleotide synthesis [29].…”
Section: Methodsmentioning
confidence: 99%
“…CD spectra were measured using a Jasco J-810 spectropolarimeter (Easton, MD). The oligonucleotides CG and CG 8Ph were prepared as previously described [24] as were the protected 8-(4-aryl)-2'-deoxyguanosine phosphoramidites needed for oligonucleotide synthesis [29].…”
Section: Methodsmentioning
confidence: 99%
“…It has been described that 8-substituted purine nucleosides are more sensitive to acidic conditions than their non-substituted analogues [1,21] and indeed we have experienced serious difficulties to remove the isopropylidene group by acid treatment without affecting the glycosidic bond. In this scenario, we considered relevant to determine the hydrolytic stability of the synthesised 8substituted inosines at different pH values.…”
Section: Hydrolitic Stability Studiesmentioning
confidence: 99%
“…There have been several amine protecting groups that have been used to protect the free amine group on the guanine ring and standard guanine phosphoramidites use an isobutyryl moiety. However the addition of a C8-aryl group onto the 2'deoxyguanosine renders the nucleoside more susceptible to acid cleavage and our group, along with another group, have demonstrated that protection using a N,N-dimethylformamidine 100,125,130 creates a more stable C8-aryl-2'-deoxyguanosine nucleoside, which is important in subsequent nucleosidic functionalization reactions as well as during DNA synthesis. Reaction with C8-aryl- Unlike the previous two reactions in the C8-aryl-2'-deoxyguanine phosphoramidite synthetic scheme, this reaction product requires purification before the phosphitylation reaction.…”
Section: B C8-aryl-2'-deoxyguanosine Protection and Functionalizationmentioning
confidence: 78%
“…[98][99][100] In addition our group has also demonstrated expertise in the synthesis of C8-aryl-2'-deoxyguanine modified nucleoside to produce C8-aryl-2'-deoxyguanine analogs with various para-substituents on the C8-aryl modification that can be incorporated into oligonucleotide sequences. 125 In general, the C8-aryl-2'-deoxyguanine modified nucleoside synthesis begins with 8-bromo-2'-deoxyguanosine synthesis prepared from 2'-deoxyguanosine and NBS which is further used in the Suzuki coupling reaction with an arylboronic acid to make C8-aryl-2'-deoxyguanosine. Subsequently, the exocyclic amine is converted to a dimethylformamidine and then the 5'-hydroxyl is converted to the dimethoxy trityl ether.…”
Section: Chapter 3: Experimental Techniques and Resultsmentioning
confidence: 99%
See 1 more Smart Citation